Penyelesaian Perkara Pidana Pencemaran Nama Baik Melalui Media Sosial Elektronik (Studi Kasus Wilayah Hukum Klaten) - Kurnianti, Heni; , Dr. Natangsa Surbakti, SH., M.Hum (2016)
This study aims to determine the completion of the criminal case of defamation through electronic social media in Klaten Jurisdiction and to determine the consideration of Klaten District Court judge in examining and deciding the case of criminal defamation. The method used is empirical juridical with descriptive research. The data source consists of primary data, interviews and secondary data, legal data primary, secondary and tertiary. Data were collected by literature study and interviews and then analyzed qualitatively. The results showed that the resolution of the criminal case of defamation through electronic social media in Klaten district police in two ways, namely by means of the Penal (repressive activities after the occurrence of criminal acts) and non penal facility, in the form of counseling for preventive action. Basic considerations Klaten District Court judge in examining and deciding the case of criminal defamation that is based on the consideration of formal and substantive considerations. Based on the facts revealed at the hearing that the fact the defendant found guilty of violating Article 27 paragraph 3 of the Law on Information and Electronic Transactions (UU ITE) and acts of defamation has fulfilled the elements of Article 310 of the Code Penal, as well as dropping imprisonment for four (4) months and a trial period of 10 (ten) months.